Performa Produksi Sapi Bali dan Peranakan Ongole yang Digemukan dengan Pakan Berbasis Sorghum - Aditya, E. L.; Priyanto, R.; Baihaqi, M.; Putra, B. W.; Ismail, M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
The objective of the research was to evaluate production performance of Bali and Ongole crossbreed (PO) cattle fed with sorghum grain base. A total 12 cattle were used for this research. Treatment were breed (Bali and Ongole crossbreed) and slaughter weight (slaughter weight group 1/SWG 1 : 250-300 kg and slaughter weight group/SWG 2 : 300-350 kg) with 3 cattle for each treatment. Parameter observed were feed conversion, average daily gain (ADG), feed consumption and final weight. The result indicated that PO cattle has better feed conversion for both group of slaughter weight than Bali cattle (P<0.05). The average feed conversion for Bali and PO cattle on SWG 1 were 14.586 and 9.064 respectively, whereas on SWG 2 were 18.566 and 9.163 respectively. In consequence the ADG of PO cattle was higher than Bali cattle (P<0.05). The ADG for PO cattle and Bali cattle (kg/day) on SWG 1 were 0.797 and 0.478 respectively, and ons SWG 2 were 0.903 and 0.418 respectively. In addition, final weight for PO cattle on SWG 2 was higher than Bali cattle (P<0.05). The average final weight (kg) for PO and Bali cattle on SWG 2 were 347.10 and 307.61. There were no significant differences on final weight of PO and Bali cattle on SWG 1. The average final weight (kg) for PO and Bali cattle on SWG 1 were 285.96 and 274.44 respectively. Feeding Sorghum silage on PO and Bali cattle have positive impact on production performance, therefore this application is suitable to apply for local farmer.